Analysis of Creative Craft SME Development Strategy in Pentahelix Perspective: (Case Study of Used Rubber Craftsmen in Binjai City) - Amanda, Putri; Syahbudi, Muhammad; Daulay, Aqwa Naser (Ilomata International Journal of Management, 2024)
Craft businesses in Binjai City do exist, but lack influence and coherence. Therefore, having the ability to innovate is very important for good management. The purpose of this study is to create a process in building a creative craft industry as an economic driver in Binjai City. We hope to build relationships between the creative craft industry and other economic sectors by assessing the potential of the City's creative craft industry and developing an action plan. This study uses a qualitative descriptive approach using the Pentahelix idea. Data collection methods used include observation, interviews, documents, and literature studies. In addition, this study combines SWOT and STP (Segmentation, Targeting, Positioning) analysis with the PentaHelix concept. Researchers produce research using SWOT and STP, it can be seen what strategies are suitable for developing a business, from the results of SWOT there is a suitable SO strategy to use so that the business can continue to grow, and from the results of STP, consumers who shop at creative craft SMEs are not impulsive buyers but shop according to their needs.